2019
DOI: 10.2106/jbjs.19.00566
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Fluids Used for the Prevention and Treatment of Orthopaedic Infections

Abstract: ➤ Intrawound irrigation is a mainstay in the prevention and treatment of surgical site infections.➤ There are 3 components of irrigation: delivery method, volume, and type of solution (with and without additives).➤ A low-pressure delivery system for a 1 to 9-L volume of solution should be used to irrigate wounds, with a greater volume indicated in the setting of contaminated or infected wounds.➤ Operative irrigation solutions are frequently supplemented with the addition of surfactants, antibiotics, or antisep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 77 publications
0
25
0
Order By: Relevance
“…Fungicidal --Viricidal Some effect MOA: mechanism of action; EPS: extracellular polymeric substances; HOCl: hypochlorous acid; CHG: Chlorhexidine gluconate. Table content reproduced with permission from Kavolus et al (2020). and 2018 international consensus meeting (ICM) on musculoskeletal infections recommend against the use of antibiotic irrigation in PJI and SSI prevention and treatment (Blom et al, 2019).…”
Section: Bactericidalmentioning
confidence: 99%
See 2 more Smart Citations
“…Fungicidal --Viricidal Some effect MOA: mechanism of action; EPS: extracellular polymeric substances; HOCl: hypochlorous acid; CHG: Chlorhexidine gluconate. Table content reproduced with permission from Kavolus et al (2020). and 2018 international consensus meeting (ICM) on musculoskeletal infections recommend against the use of antibiotic irrigation in PJI and SSI prevention and treatment (Blom et al, 2019).…”
Section: Bactericidalmentioning
confidence: 99%
“…Although CHG has demonstrated efficacy against grampositive and gram-negative pathogens (Van Meurs et al, 2014), other studies have shown its antibacterial effect offset by increased host tissue toxicity (Liu et al, 2018). Higher CHG concentrations (0.5 % to 2 %) have been shown to substantially reduce human fibroblast, myoblast, osteoblast, and stromal cell survival (Kavolus et al, 2020;Van Meurs et al, 2014). Furthermore, some studies report antibiotic resistance after CHG exposure, as well as Enterococcus faecium and Pseudomonas resistance to CHG itself (Kavolus et al, 2020).…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact DAIR methodology that provides the greatest success for immunosuppressed patients remains unclear. Irrigation with Betadine (Avrio Health L.P.; Stamford, CT, USA) and chlorhexidine seems to be the most effective approach in preventing infection recurrence [30,31]. A 2-stage DAIR approach with the use of antibiotic-eluting beads may help improve results in this patient population [32].…”
Section: Diagnosis Treatment and Postoperative Complicationsmentioning
confidence: 99%
“…27,28 The need for improved preventive approaches is so severe that many surgeons use antibacterial strategies with known toxic effects on local cells/tissues (excessive vancomycin powder, soap washes, etc.). 29,30 However, clinical studies suggest that even perfect adherence to infection prevention protocols are unlikely to reduce the incidence of infection in elective surgeries below 1%-2% (the current rates of PJI). 31,32 Further advances in sterile technique and even the use of robotic surgery will not remove the greatest source of microbial contamination: the patient.…”
Section: Can the Microbiome Help Prevent Periprosthetic Joint Infecmentioning
confidence: 99%